2009
DOI: 10.2741/335
|View full text |Cite
|
Sign up to set email alerts
|

Sanggenon C decreases tumor cell viability associated with proteasome inhibition

Abstract: Several flavonoids have been reported to be proteasome inhibitors, but whether prenylated flavonoids are able to inhibit proteasome function remains unknown. We report for the first time that Sanggenon C, a natural prenylated flavonoid, inhibits tumor cellular proteasomal activity and cell viability. We found that (1) Sanggenon C inhibited tumor cell viability and induced cell cycle arrest at G0/G1 phase; (2) Sanggenon C inhibited the chymotrypsin-like activity of purified human 20S proteasome and 26S proteaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…After MIB1 was once overexpressed, it may want to needless to say block the upregulation of DAPK1 precipitated with the aid of SC. Previous findings confirmed that SC was once in a position to accumulate proteasome substrate protein p27 in a dose‐dependent manner in general precipitated proteasome inhibition in murine H22 and P388 cell strains 15 . Similarly, our results indicated that SC therapy decreased MIB1‐mediated DAPK protein degradation in a dose‐dependent manner in GBM cells.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…After MIB1 was once overexpressed, it may want to needless to say block the upregulation of DAPK1 precipitated with the aid of SC. Previous findings confirmed that SC was once in a position to accumulate proteasome substrate protein p27 in a dose‐dependent manner in general precipitated proteasome inhibition in murine H22 and P388 cell strains 15 . Similarly, our results indicated that SC therapy decreased MIB1‐mediated DAPK protein degradation in a dose‐dependent manner in GBM cells.…”
Section: Discussionsupporting
confidence: 88%
“…Interest in SC's anti‐cancer properties has grown recently as a result of in vitro and animal research showing that it slows tumor growth, including cell cycle and cell death. In human K562 cancer cells, SC displayed strong inhibitory effects by inducing cell cycle arrest and cell death via inhibiting tumor cellular proteasomal activity 15 . In addition, another study documented that SC could dose‐dependently induce cell death by activating caspase3 and caspase9 signaling 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Kuwanon Y was shown to inhibit protein kinase C (PKC) with an IC 50 value of 15 μM [ 106 ]. Sanggenon C ( 13 ) inhibited tumour cellular proteasomal activity and cell viability via induction of cell cycle arrest and cell death, but also induced necrotic cell death in cancer cells, which could limit the clinical potential of Sanggenon C [ 107 ]. Sanggenons C and O ( 13 and 14 ) and kuwanon J were evaluated using luciferase reporter assay and were found to inhibit hypoxia-induced HIF-1α accumulation in a dose-dependent manner in human hepatocellular carcinoma cell-line Hep3B cells (IC 50 = 1.03 μM, for sanggenon O ( 14 )) [ 108 ].…”
Section: Biological Activity Of Mulberry Daasmentioning
confidence: 99%
“…Compounds isolated from M. alba exhibit antitumor activities by different mechanisms, where kuwanons inhibit hypoxia-induced HIF-1α accumulation [44], and inhibit protein kinase C [45]. Sanggenons also inhibit hypoxia-induced HIF-1α accumulation [44], induce internucleosomal DNA fragmentation [46], induce cell cycle arrest at G0/G1 phase, and inhibit the chymotrypsin-like activity [47].…”
Section: Antitumor Activitymentioning
confidence: 99%